Reduction of pesticide residues from tomatoes by low intensity electrical current and ultrasound applications - Cengiz, Mehmet Fatih; Baslar, Mehmet; Basancelebi, Onur; Kilicli, Mahmut (ELSEVIER SCI LTD, 2018)
In this study, effects of low intensity electrical current (EC) and ultrasound (US) treatments on the reduction of some important pesticides (captan, thiamethoxam and metalaxyl) residues in tomato samples were investigated. Three different currents (200, 800 and 1400 mA) of EC were applied at various time intervals (2, 4, 6, 8 and 10 min). Two kinds of US treatments including ultrasonic bath (UB) at 40 kHz and ultrasonic probe (UP) at 24 kHz were tested for the determination of US effectiveness. In addition, synergistic effects of US on EC treatments were evaluated. The most effective conditions for reduction of captan, thiamethoxam and metalaxyl residues were 1400 mA + 40 kHz, 800 mA + 24 kHz and 1400 mA + 24 kHz, respectively. The residues of captan, thiamethoxam and metalaxyl were reduced in the order of 94.24%, 69.80% and 95.06% by using these combinations. EC and US strategies can be considered as effective treatments in industrial scale in order to remove the pesticide residues from vegetables.
Keywords: Low intensity electrical current; Pesticide residue; Tomato; Ultrasound; DOPED DIAMOND ELECTRODES; PHOTO-FENTON; DEGRADATION; OXIDATION; WATER; REMOVAL; PERSPECTIVES; TECHNOLOGY; PARAMETERS; KINETICS; Chemistry; Food Science & Technology; Nutrition & Dietetics